Analysis Of Principal Management in Improving Teacher Pedagogical Competence In Inclusive Schools: Analisis Manajemen Kepala Sekolah Dalam Meningkatkan Kompetensi Pedagogik Guru di Sekolah Inklusi - Andriani, Nurdiana Faizah; Fauji, Imam (Indonesian Journal of Innovation Studies, 2026)
General Background: School principal management is important for developing teachers’ pedagogical competence in inclusive schools. Specific Background: At SD Muhammadiyah 1 Candi, teacher development is implemented through classroom management training, educational technology, innovative learning, teacher working groups (KKG), differentiated instruction, and inclusive education forums. Knowledge Gap: The management process, implementation challenges, and solutions within this inclusive-school context require further examination. Aims: This study analyzes the POAC-based management of teacher pedagogical competence and identifies implementation challenges and solutions. Results: Qualitative descriptive findings show that programs follow planning, organizing, actuating, and controlling processes, while challenges include limited time, tight schedules, resource and facility constraints, and varied teacher motivation and engagement. Novelty: The study describes the continuous POAC-based management of multiple teacher development programs in an inclusive elementary school. Implications: Flexible scheduling, digital technology, external partnerships, incentives, moral support, and teacher participation in planning can support program implementation. Key Findings Highlights Continuous POAC management structures teacher development programs in an inclusive school. Teacher development covers classroom management, educational technology, innovative learning, KKG, differentiated instruction, and inclusive education forums. Limited time, resources, facilities, Keywords : School Principal Management, Teacher Pedagogical Competence, POAC, Inclusive School, Teacher Development